Multi-scale computational screening of all-silica zeolites for adsorptive separation of ternary (H2S/CO2/CH4) mixtures - Yoon, Sunghyun; Hassan, Muhammad; Chung, Yongchul G. (Chemical engineering journal (Lausanne, Switzerland : 1996), 2024)
•Computational modeling was conducted for H2S and CO2 removal from a ternary mixture (H2S/CO2/CH4).•Process and economic optimization showed APC-type zeolites are the best performing.•Orientation of adsorbed CO2 in APC zeolites leads to the selective adsorption of both H2S and CO2. Natural gas (NG) is a complex mixture of CH4, H2S and CO2, and the presence of H2S and CO2 molecules are detrimental to direct utilization of NG for energy generation. Adsorptive separation is a promising avenue to remove H2S and CO2 from a mixture NG however, the identification of high-performing adsorbents that could simultaneous remove both H2S and CO2 is a challenge. In this study, we carried out multi-scale computational modeling integrating molecular simulations, process modeling, and optimization to screen already-synthesized zeolites for the simultaneous removal of H2S and CO2 from a ternary mixture of H2S, CO2, and CH4. We performed the process cycle optimization using a genetic algorithm for three zeolites (APC-0, APC-2, and ATV-1) which show good match between EDSLF (extended dual-site Langmuir–Freundlich) and mixture GCMC (grand canonical Monte Carlo) results. Process optimization revealed the superior acid-gas removal capabilities of APC-0 and APC-2 over ATV-1. We also compared the simulation results obtained from EDSLF models with the results obtained using the Ideal Adsorbed Solution Theory (IAST). We found the optimized decision variable distributions are not always the same for the two different approaches. Economic optimizations on APC-type zeolites showed that the feed composition affects the characteristics of the mixture adsorption isotherms, which in turn affects the energy consumption trends of the two zeolites. Finally, we carried out molecular simulation to understand the impact of molecule siting on the process performance. We found that the siting of adsorbed CO2 within the zeolite’s pores impacts the adsorption behavior of CH4 for ATV-1 which led to low overall performance in the process-level performance of AVT-1 compared to APC-type zeolites.